The Role and Challenges of Islamic Religious Education in the Age of Globalization - Riza Rahmawati; Rosita Rosita; Masduki Asbari (AGUSPATI RESEARCH INSTITUTA, 2022)
Islam obliges its followers to be learned and educated people. It is hoped that educated people in this global era will increase whereas uneducated people will decrease in light of the changing time. Islamic education guides its students in their development in both physical and spiritual dimensions towards the formation of noble personality and morality. The objectives of Islamic education according to the Qur’an include: (1) to explain the position of students as a human beings among other creatures and their responsibility in this life; (2) to explain their position as social beings and their responsibility in societal life; (3) to explain the relationship between human being and the nature and their task to know the wisdom of creation; and (4) to explain the relationship between human beings and the Creator of the universe.